PROGRAM KEMITRAAN WILAYAH (PKW) DIKECAMATAN LIUKANG TUPABBIRING UTARA KABUPATEN PANGKEP - Jamaluddin Jompa; Asmi Citra Malina; Rahmi Rahmi; Asni Anwar; Andi Nur Arifah (Ngayah: Majalah Aplikasi IPTEKS, 2018)
One sub-district that has the potential for marine and fisheries as well as superior tourism in Pangkajene and Islands regencies is Liukang Tupabbiring Utara sub-district. Superior fisheries potential in Mattiro Baji Village and Mattiro Bombang Village in Liukang Tupabbiring Utarasub-district is an opportunity to invest. Small islands in these two villages generally face various obstacles and problems as a consequence of isolation and the difficulty of access to service centers, education, and the economy. Therefore, UNHAS in collaboration with the Universitas Muhammadiyah Makassar and the Regional Government of Pangkep Regency agreed to try to overcome and reduce this problem through the Regional Partnership Program (PKW) in Liukang Tupabbiring Utara sub-district, Pangkep Districts. The Regional Partnership Program (PKW) has produced several activities, namely: Training in making environmentally friendly fishing equipment and sustainable fisheries, post-harvest handling & processing of seaweed and fish products, PIRT management, product packaging and exhibitions, business development of souvenirs and coverage in online media, simple bookkeeping training and marketing for handicraft businesses on Saugi Island, health data mapping, training in waste processing, advocacy for the formation of cooperatives. The implementation of this program can not only improve the economy and quality of public health, but also can encourage environmental quality improvement, so that natural resources can be managed sustainably by better human resources.